Approaches to estimating the health state dependence of the utility function - Amy Finkelstein; Erzo F.P. Luttmer; Matthew J. Notowidigdo (Institute for the Study of Labor (IZA), 2009)
If the marginal utility of consumption depends on health status, this will affect the economic analysis of a number of central problems in public finance, including the optimal structure of health insurance and optimal life cycle savings. In this paper, we describe the promises and challenges of various approaches to estimating the effect of health on the marginal utility of consumption. Our basic conclusion is that while none of these approaches is a panacea, many offer the potential to shed important insights on the nature of health state dependence.
urn:nbn:de:101:1-20090119213
Keywords: D12; I1; 330; State dependence; health; insurance; marginal utility; Nutzenfunktion; Gesundheit; Konsumtheorie; Zeitpräferenz; Krankenversicherung; Lebenszyklus; Hysteresis